Bisemivalues for bicooperative games. (3rd June 2018) - Domènech, Margarita; Giménez, José Miguel; Puente, María Albina
Abstract: We introduce bisemivalues for bicooperative games and we also provide an interesting characterization of this kind of values by means of weighting coefficients in a similar way as it was given for semivalues in the context of cooperative games. Moreover, the notion of induced bisemivalues on lower cardinalities also makes sense and an adaptation of Dragan's recurrence formula is obtained. For the particular case of ( p, q )-bisemivalues, a computational procedure in terms of the multilinear extension of the game is given.